Rancang Bangun Ruang Baca Digital Berbasis Web Pada Perpustakaan Desa Mengwi - Putra, I Putu Gede Andika; Adnyana, I Made Budi; Putri, Dian Rahmani (Universitas Tabanan, 2024)
One innovation that can be done to increase people's interest in reading is by utilizing technology, namely by creating a digital reading room information system. This system was designed using Data Flow Diagrams, Entity Relationship Diagrams, Table Structure, and Interface Design. The programming language uses HTML, PHP, CSS, Laravel Framework and Laravel Admin as its framework. The system built has the function of managing book and user data and has the main function of making it easier to read books in the Mengwi Village library. The black box testing results show valid results from 23 test items from 3 existing user accesses. The results of the SUS questionnaire gave a score of 82.75, which is classified as Acceptable, has Grade B and is Excellent. Users feel they can accept the system and get a grade on the B scale with a good adjective rating. In future, features can be developed that can make it easier for users to read books and share the books they own, and the system can also be implemented into a mobile application.